Expressive Writing Dalam Penurunan Tingkat Stres Akademik Mahasiswa - Andi Siti Azizah Dalauleng; Widyastuti Widyastuti; Ahmad Ridfah (CV. ULIL ALBAB CORP, 2024)
Students who are working on their thesis often experience stress due to demands to immediately complete their studies. This makes students feel easily anxious and afraid. One way students deal with stress is by writing about how they feel. This can be referred to as expressive writing. This study aims to determine the effectiveness of expressive writing on reducing academic stress levels for students of the Faculty of Psychology UNM. 13 participants were divided into the experimental group and the control group. This research uses quantitative methods with an experimental approach in the form of Pretest-posttest Control Group Design. This study showed a decrease in the mean academic stress score of the experimental group, from 63,3 to 47,3 and an increase in the mean academic stress score of the control group, from 55,3 to 57,8. The results of hypothesis testing also show that expressive writing is effective in reducing students' academic stress levels (t = 0.500, p = 0.004 < 0.05). Expressive writing which is done by writing topics related to emotional problems and trauma is proven to be able to reduce student academic stress. The result of this research can be a consideration for education provides to apply expressive writing for students who are working on their theses.